Anthrone-spirolactam and quinoline hybrid based sensor for selective fluorescent detection of Fe(3+)ions - Darole, Ratanamala S.; Christopher Leslee, Denzil Britto; Mukherjee, Anagh; Gonnade, Rajesh G.; Karuppannan, Sekar; Senthilkumar, Beeran (2020)
The synthesis of a novel, and highly selective Fe(3+)ion sensor based on anthrone-spirolactam and its quinoline hybrid ligand is reported. The designed ligand displayed selective detection of Fe(3+)ions with enhanced fluorescence emission. The complexation of Fe(3+)ion led to a red shift of 32 nm from 420 nm to 452 nm, and a several fold increase in intensity with fluorescent green emission. The complexation (detection) of Fe(3+)ions with ligand resulted in chelation enhanced fluorescence and intramolecular charge transfer through the inhibition of C=N isomerization. This hybrid sensor shows high sensitivity and selectivity, spontaneous response, and works on a wide pH range a minimum detection limit of 6.83 x 10(-8)M. Importantly, the sensor works through the fluorescence turn-on mechanism that overcomes the paramagnetic effect of Fe(3+)ions. The binding mechanism between the ligand and the Fe(3+)ions was established from the Job's plot method, optical studies, Fourier transfor infrared spectroscopy, NMR titration, fluorescence life-time studies, and density functional theory optimization. The sensor displayed excellent results in the quantification of Fe(3+)ions from real water samples. Furthermore, due to its biocompatibility nature, fluorescent spotting of Fe(3+)ions in live cells revealed its bioimaging applications.
Keywords: anthrone-spirolactam-quinoline; Cell imaging; fluorescence; intramolecular charge transfer; iron